Kekuatan aktivitas pemasaran di media sosial dalam meningkatkan niat beli berulang produk Fore Coffee di Indonesia - Rahmadini, Marzela Novia; Nurhadi, Mochamad; Djunaedi, Arif Zeinfiki (Journal of Management and Digital Business, 2025)
The presence of various foreign and local coffee products has contributed to the growing number of coffee shops. Coffee consumption has become an integral part of today’s modern lifestyle. This study aims to analyze the structural model of marketing activities on social media, brand equity, value awareness, and brand loyalty in enhancing the repurchase intentions of Fore Coffee consumers in Indonesia. The population of this study consists of all Fore Coffee consumers in Indonesia, particularly those in major cities. The sampling technique used was purposive sampling. Data were collected through a questionnaire distributed via Google Forms, with a total of 158 respondents who met the research criteria. The data were analyzed using PLS-SEM. The results show that social media marketing activities have a positive and significant impact on brand equity, repurchase intentions, brand loyalty, and value awareness related to Fore Coffee. Furthermore, brand equity also has a positive and significant influence on repurchase intentions. Value awareness has a strong positive effect on brand loyalty. Likewise, brand loyalty positively and significantly influences the repurchase intentions of Fore Coffee consumers in Indonesia.